Unregistered Marriage Between Indonesian Citizens and Foreign Citizens With the Legal Perspective of Marriage in Indonesia - Muhammad Ngizzul Muttaqin (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2020)
The practice of unregistered marriage between Indonesian citizens and foreign nationals always raises legal problems, both the law of marriage and the legal consequences of the marriage. This article aims to provide concrete legal solutions and steps to the practice of unregistered marriage between Indonesian citizens and foreign nationals. This study used literature research with qualitative descriptive methods, through a normative legal approach. The results show that unregistered marriage is a social symptom of modern society which always occurs in the practice of today’s society. Although unregistered marriage is not specifically regulated in the practice of mixed marriages, it often occurs and must be anticipated. The solution is that there are three legal options that can be taken: first, if the person concerned is domiciled in Indonesia and intends to become an Indonesian citizen, then s/he can register the marriage with the employee who registers the marriage and performs the marriage certificate according to the provisions. Second, if the person concerned is living abroad but wants to become an Indonesian citizen, then s/he can take legal steps by registering the marriage and marriage certificate at the Indonesian Embassy. Third, if the person concerned is domiciled and wants to become a resident of a foreign country, then the person concerned must take the legal route that has been determined in that country. Thus, family law in Indonesia can be adaptive and responsive to the dynamics of social change.